2016
DOI: 10.1021/acs.est.5b06050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Coatings, Humidity and Aerosol Acidity on Multiphase Chemistry of Isoprene Epoxydiols

Abstract: Multiphase chemistry of isomeric isoprene epoxydiols (IEPOX) has been shown to be the dominant source of isoprene-derived secondary organic aerosol (SOA). Recent studies have reported particles composed of ammonium bisulfate (ABS) mixed with model organics exhibit slower rates of IEPOX uptake. In the present study, we investigate the effect of atmospherically relevant organic coatings of α-pinene (AP) SOA on the reactive uptake of trans-β-IEPOX onto ABS particles under different conditions and coating thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(117 citation statements)
references
References 72 publications
(171 reference statements)
6
111
0
Order By: Relevance
“…In other words, RH does not change the partition of IEPOX in our experimental conditions. This is consistent with the result of Riva et al (2016) that water has a weaker impact on IEPOX-derived SOA yield.…”
Section: Isoprene-h 2 O 2 and Isoprene-o 3 Systemssupporting
confidence: 92%
“…In other words, RH does not change the partition of IEPOX in our experimental conditions. This is consistent with the result of Riva et al (2016) that water has a weaker impact on IEPOX-derived SOA yield.…”
Section: Isoprene-h 2 O 2 and Isoprene-o 3 Systemssupporting
confidence: 92%
“…A recent study by Riva et al . [] utilized single‐particle mass spectrometry and directly demonstrated that IEPOX uptake by pure ammonium bisulfate and ammonium sulfate particles is a volume‐controlled process. Volume‐controlled IEPOX uptake by pure sulfate particles results in particles with uniform concentration of IEPOX‐derived SOA across a wide range of sizes, as shown by Riva et al .…”
Section: Biogenic Emissions and Soa Formationmentioning
confidence: 99%
“…Volume‐controlled IEPOX uptake by pure sulfate particles results in particles with uniform concentration of IEPOX‐derived SOA across a wide range of sizes, as shown by Riva et al . []. One challenge to incorporating IEPOX reactive uptake into models is that the presence of organic coatings may also affect the kinetics.…”
Section: Biogenic Emissions and Soa Formationmentioning
confidence: 99%
“…In addition, hydroxyl radical concentrations can also decrease because of titration by NO 2 (Valin et al, 2013;Rohrer et al, 2014). An increase in total organic mass concentration could possibly contribute to a decrease in IEPOX-derived PM production by kinetically limiting the uptake of IEPOX (Gaston et al, 2014;Lin et al, 2014;Riva et al, 2016a). The dominant effect of the urban plume, however, seems to be that of shifting the fate of ISOPOO radicals through the increase in NO, thereby significantly decreasing the production of ISOPOOH (Liu et al, 2016a) (Sect.…”
Section: No As a Modulator Of Iepox-derived Pm Productionmentioning
confidence: 99%